On risk induced by technical change - Burak Ünveren (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2017)
Purpose: The purpose of this paper is to analyze the efficiency loss due to incomplete financial markets when risk is induced by technological uncertainty. Design/methodology/approach: A worker-capitalist general equilibrium model is developed. It is assumed that future technical change is a stochastic event, causing uncertainty in future relative prices. Then the model is calibrated to the US data. Findings: Our first finding is theoretical: the competitive equilibrium is Pareto-inefficient. Then we numerically calculate the taxes that make all individuals better-off at the calibrated parameter values. The results clearly show how the burden of taxation should be shared among workers and capitalists when the government uses redistribution of income as a tool of mitigating the loss of efficiency due to technological shocks. Research limitations/implications: The model is obviously a stripped-down version of reality, and hence, the results should be taken with a grain of salt as the numerical computations would be definitely sensitive to certain rich details of real life that are neglected in this study. Originality/value: The results show that the total amount of employment, and production are not affected by optimal taxation, which is a surprising result. Indeed, the inefficiency is primarily caused by the distribution of labor supply among individuals. The optimal taxes are also numerically computed.
Keywords: C68; D52; H21; 330; Incomplete markets; Constrained efficiency; redistribution